A pioneer of Nordic conservation: the environmental literacy of A. E. Nordenskiöld (1832–1901) - Niemi, Seija A. (fi=Turun yliopisto|en=University of Turku|, 2018)
This doctoral thesis will show that Nils Adolf Erik Nordenskiöld (1832-1901), a Finnish born Swedish scientist and explorer, was an environmentally literate person before the concept of environmental literacy was formulated in the 1960s. During his Arctic expeditions, between 1858 and 1883, Nordenskiöld observed destructive processes in the natural world caused by humans and he took appropriate action to maintain, restore, or improve the health of the systems in nature: features, which are substantive qualifications of environmental literacy. He presented environmentally literate ideas in his writings, especially in his short essay, written in 1880 and entitled “Förslag till inrättandet af Riksparker i de nordiska länderna.” This essay has subsequently gained a reputation as one of the founding texts in the history of early Nordic conservation. This work brings together scholarship in environmental history, economic history, the history of ideas and ethnology, the history of science and the history of ideologies; the study of explorations, conservation and the Arctic regions. It is the first research to be carried out on Nordenskiöld from the point of view of environmental history. The articles that make up this dissertation will discuss different sides of Nordenskiöld’s life and career, his interests and environmentally literate expressions. They also analyse his position in the history of Nordic conservation. A conservation movement can be seen as a military-like organisation to protect nature. Nordenskiöld wanted to fight against new kinds of infrastructure and technological innovations, which threatened pristine nature and he wanted to prevent any ecological disasters. This is why he suggested the establishment of national parks in which pristine nature could be saved in open-air museums to be enjoyed by future generations. Many of his colleagues, in Sweden, Finland and abroad, shared his concerns and, continued to argue for conservation after his death. The first nine national parks in Sweden were established in 1909 in places recommended by Nordenskiöld in “Förslag”: “publicly owned land […] which yield insignificant or no profit”. This doctoral dissertation proves that the concept of environmental literacy can be used in a case study in a historical perspective. Nordenskiöld’s example helps us to understand the important role of every individual in the history of the environment: the fact that everybody has an impact on history and on the environment.

Tämä väitöskirja osoittaa, että Nils Adolf Erik Nordenskiöld (1832-1901), Suomessa syntynyt ja Ruotsissa uransa luonut tiedemies ja tutkimusmatkailija, oli ympäristönluku-taitoinen henkilö ennen kuin ympäristönlukutaito käsite syntyi 1960-luvulla. Hän havaitsi vuosien 1858 ja 1883 välillä tekemillään arktisilla tutkimusmatkoilla ihmisten aikaan-saamia tuhoja luonnossa, joiden perusteella hän ryhtyi toimiaan niin, että pystyisi ylläpitämään, säilyttämään ja parantamaan luonnossa vallitsevaa tervettä tasapainoa: toimenpiteitä, jotka ovat ympäristön lukutaidon peruselementtejä. Ajatukset, joita hän ilmaisi teksteissään, kertovat, että hän oli ympäristönlukutaitoinen. Varsinkin hänen vuonna 1880 kirjoittamansa lyhyt tutkielma “Förslag till inrättandet af Riksparker i de nordiska länderna” on tästä hyvä esimerkki. Tämä tutkielma on vuosien kuluessa saanut keskeisen aseman pohjoismaisen luonnonsuojelun historiassa. Tässä väitöskirjassa ympäristöhistoria, taloushistoria, aatehistoria ja kansatiede, tieteen- ja maailmankatsomushistoria yhdistyvät tutkimusmatkojen, luonnonsuojelun ja arktisten alueiden tutkimukseen. Tämä on ensimmäinen ympäristöhistoriallinen tutkimus Norden-skiöldistä. Väitöskirjan artikkelit kertovat Nordenskiöldin elämästä ja urasta, hänen kiinnostuksen kohteistaan ja ympäristönlukutaidostaan. Niissä myös analysoidaan, mikä hänen asemansa oli ja on pohjoismaisen luonnonsuojelun historiassa. Luonnonsuojeluliikettä voi nimittää taisteluksi luonnon puolesta. Nordenskiöld halusi taistella uudenlaista infrastruktuuria ja teknistä kehitystä vastaan, jotka uhkasivat alkuperäistä luontoa, ja hän halusi estää ekologiset katastrofit. Siksi hän ehdotti, että perustettaisiin kansallispuistoja, joissa alkuperäinen luonto säilyisi seuraavien sukupolvien iloksi ulkoilmamuseoissa. Monet hänen työtoverinsa Ruotsissa, Suomessa ja muissa maissa jakoivat hänen huolensa ja jatkoivat hänen kuolemansa jälkeen työtä luonnonsuojelun hyväksi. Vuonna 1909 Ruotsin ensimmäiset kansallispuistot perustettiin paikkoihin, joita Nordenskiöld suositteli ”Förslagissaan”: ”valtion omistamille maille […] jotka tuottavat vain vähän tai ei ollenkaan taloudellista hyötyä.” Ympäristön lukutaito käsitettä voidaan tämän väitöskirjan perustelujen mukaan käyttää yhden historiallisen henkilön tutkimuksessa. Nordenskiöldin esimerkki saa meidät myös ymmärtämään, että jokainen yksilö on tärkeä ympäristön historiassa: että jokaisella yksilöllä on oma vaikutuksensa historiaan ja ympäristöön.